A study based on a survey of overall Australian labour force, occupation, industry of employment comparing to Victorian (“Victoria” – a province in Australia) suburbs - Karim, Mehnaz (© 2014 Omniscience: A multidisciplinary journal, 2016)
This article was published in the Omniscience: A multidisciplinary journal [© 2014 Omniscience ] The Article's website is at: http://www.sciencedirect.com/science/article/pii/016781169400020O